DAWAM RAHARJO (Ekonomi Islam Antara Kapitalisme dan Sosialisme) - Abbas, Pirhat (Media Akademika, 2009)
The capitalism economy system which hold im`tiative is individually or private and the socialism economy system which hold im-tiatt.ve is government. The Islamic economy system is combination between methodic and systematic of Islamic teaching in the field o, f economy.